Combined medial and lateral bucket handle meniscus tears with associated complete anterior cruciate ligament tear-a case report - Sohail, Muhammad Amir; Bashir, Amna; Umair Ul Hassan (Journal of the Pakistan Medical Association, 2023)
The majority of meniscal tears in bucket handles are associated with anterior cruciate ligament (ACL) impairment. Its a rare condition which is rarely encountered when the meniscus has a bucket handle on both sides of the compartment. Here we present the case of a 28-year-old male cricket player with a total ACL rupture, a double Posterior Cruciate ligament (PCL) sign on MRI (Magnetic Resonance Imaging), an uncommon occurrence of a complex bucket handle rupture of the medial meniscus with a double PCL sign. It was a complete ACL tear and displaced bucket handle medial meniscus that was also visible on the magnetic resonance imaging. In this report, double PCL sign was shown on MRI and that was confirmed during the arthroscopic procedure. Keywords: Complete ACL tear, combined medial & lateral bucket handle, meniscus tears.